Thermodynamic and kinetic modeling of oxide precipitation in nanostructured ferritic alloys. (1st June 2015) - Barnard, L.; Cunningham, N.; Odette, G.R.; Szlufarska, I.; Morgan, D.
Abstract: The mechanical properties and radiation tolerance of nanostructured ferritic alloys rely on a dense population of nanometer-scale Y–Ti oxides. The stability of these nano-oxides during extended service is critical in high temperature applications. Here, a model framework is developed for the thermodynamics and kinetics of Y–Ti oxide nucleation, growth and coarsening. The model, which is based upon available thermodynamic and kinetic data as well as key density functional theory calculations, shows that nano-oxide nucleation and growth are highly driven and that pipe diffusion is the dominant mode of their coarsening, in agreement with previous analyses of experimental high temperature data. The model predicts that the nano-oxides are thermally stable for 80 or more years below 1175 K. This analysis also provides insights into the effect of O and Ti on nano-oxide sizes, and on optimization of alloy microstructure.